Theory-driven measurement of the content of prayer: Polish revision of S. Huber's Content of Prayer Scale. Issue 6 (2nd July 2020) - Piotr Bartczuk, Rafał; Zarzycka, Beata
ABSTRACT: The empirical study of prayer has remained an underdeveloped field in the Polish psychology of religion. The lack of adequate and psychometrically sound methods to measure prayer has also been observed. The Polish adaptation of the Content of Prayer Scale (CoP) by Huber is designed to meet this gap. The CoP builds upon the theoretical approach, which combines theological and psychological concepts of prayer. The aim of this study was to translate, adapt and validate the CoP into Polish culture, as well as to examine whether there is the possibility of integrating these two concepts of prayer. In three studies (total N = 2488) the internal structure of the CoP was explored, revised version of the method was established, its internal structure was confirmed and cross-validated and its reliability and validity were examined. The shortcomings of the theoretical approach proposed by Huber are discussed.